2020
DOI: 10.1007/s10637-020-01032-y
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy modulating agents as chemosensitizers for cisplatin therapy in cancer

Abstract: Summary Although cisplatin is one of the most common antineoplastic drug, its successful utilisation in cancer treatment is limited by the drug resistance. Multiple attempts have been made to find potential cisplatin chemosensitisers which would overcome cancer cells resistance thus improving antineoplastic efficacy. Autophagy modulation has become an important area of interest regarding the aforementioned topic. Autophagy is a highly conservative cellular self-digestive process implicated in response to multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 138 publications
(335 reference statements)
0
29
0
Order By: Relevance
“…Generally, there is a strong relationship between autophagy and cisplatin resistance. Recently, Gąsiorkiewicz et al reviewed autophagy-modulating compounds that chemosensitize for cisplatin in cancer therapy [ 54 ]. Among these compounds are classical autophagy inhibitors, compounds with specific autophagy-related targets, and natural compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there is a strong relationship between autophagy and cisplatin resistance. Recently, Gąsiorkiewicz et al reviewed autophagy-modulating compounds that chemosensitize for cisplatin in cancer therapy [ 54 ]. Among these compounds are classical autophagy inhibitors, compounds with specific autophagy-related targets, and natural compounds.…”
Section: Discussionmentioning
confidence: 99%
“…More efforts in revealing anti-tumor activity of CP revealed that CP has the capacity of internalization in organelles, such as endoplasmic reticulum (ER), mitochondrion, lysosomes, and nucleus. This demonstrates that, in addition to DNA damage, CP can induce cell death by impairing homeostasis of vital organelles, such as ER and mitochondrion [19,20]. However, this impact may negatively affect anti-tumor activity of CP.…”
Section: Introductionmentioning
confidence: 96%
“…In order to increase the therapeutic efficacy and reduce the side effects, CDDP is commonly used in combination with other drugs [ 51 ]. In this context, chloroquine (CQ), which has long been used as an anti-malarial and anti-rheumatic drug, sensitizes cancer cells to chemotherapeutic drugs through the prevention of autophagy [ 61 , 62 , 63 , 64 ]. As both CDDP and CQ are nonselective and can damage healthy tissues, reducing their effective doses and increasing delivery into tumor cells is key and can be accomplished by the encapsulation of the drugs in nanoparticles [ 30 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, while simultaneous treatment with free drugs had a huge impact on both tumor and non-tumor cells, simultaneous treatment with HDLDBC-bMPA(CQ) or HDLDBC-bGMPA(CQ) and free CDDP resulted in high levels of cytotoxicity only against tumor cells. A possible explanation of this effect could be the reduced ability of Fdh to retain CQ encapsulations compared to tumor cells, as well as changes induced by cisplatin on membrane properties that reduce drug uptake and alter vesicular trafficking [ 62 , 88 , 89 ]. This opens the possibility of safely using the drugs simultaneously to achieve greater tumor cell killing without reducing the concentrations [ 85 , 90 ].…”
Section: Discussionmentioning
confidence: 99%